Case report: The outcomes of neoadjuvant immunotherapy combined with chemotherapy in pulmonary sarcomatoid carcinoma: case series and literature review - Guo, Xiaokang; Wang, Jingjing; Li, Daosheng; Wang, Bin; Zhu, Hui; Guo, Hongbo (Frontiers in Immunology, 2024)
BackgroundPulmonary sarcomatoid carcinoma (PSC) is a highly aggressive malignancy with a significant risk of recurrence even after surgical intervention, leading to a dismal prognosis. In recent years, perioperative immunotherapy has demonstrated promising results in resectable non-small cell lung cancer (NSCLC). However, there is a lack of studies reporting the efficacy of perioperative immunotherapy in PSC.Case presentationWe report the clinical outcomes of four patients diagnosed with locally advanced PSC who underwent neoadjuvant immunotherapy in combination with chemotherapy from 2021 to 2023 in our hospital. Prior to surgery, these patients received 2 to 4 cycles of neoadjuvant treatment. Post-treatment imaging assessments indicated a partial response (PR) in all cases, and each patient successfully achieved R0 resection. Pathological evaluations demonstrated significant pathological responses: one patient attained Pathological Complete Response (PCR), two patients exhibited Major Pathological Response (MPR), and one patient showed PR. Currently, all four patients remain alive without evidence of tumor progression. Notably, the patient who achieved PCR has maintained a disease-free survival (DFS) exceeding 32 months post-surgery, while their event-free survival (EFS) has surpassed 36 months.ConclusionsNeoadjuvant immunotherapy in combination with chemotherapy has provided new promise for the treatment of locally advanced PSC with surgical potential. But these findings still need to be verified by further prospective researches.